2021
DOI: 10.3390/polym13030316
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Pore-Selective Metal-Nanoparticle-Functionalized Honeycomb Films via the Breath Figure Accompanied by In Situ Reduction

Abstract: Honeycomb films pore-filled with metal (Au, Ag, and Cu) nanoparticles were successfully prepared by combining the breath figure method and an in situ reduction reaction. First, a polyhedral oligomeric silsesquioxane (POSS)-based star-shaped polymer solution containing metal salt was cast under humid conditions for the formation of honeycomb films pore-filled with metal salt through the breath figure method. The morphology of the honeycomb films was mainly affected by the polymer molecular structure and the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The addition of Fe 3+ significantly reduced the porosity and pore area of the film surface, which was attributed to the fact that the chelation between Fe 3+ , tannin, and CMC reduced the distance between PLA molecules. Furthermore, there was about 2% FeCl 3 contained in both samples, and the solvation of FeCl 3 was thought to increase the surface energy of the droplets, consequently reducing their volume [ 30 ]. Compared to the CMC/TA−PLA/Fe ( Figure 1 D1) film, the pores on the surface of the CMC−PLA/Fe ( Figure 1 C1) film were smaller, with a porosity of only 3.12%, which was attributed to the limited cross−linking rate of CMC with Fe 3+ compared to the rapid cross−linking of tannins with Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…The addition of Fe 3+ significantly reduced the porosity and pore area of the film surface, which was attributed to the fact that the chelation between Fe 3+ , tannin, and CMC reduced the distance between PLA molecules. Furthermore, there was about 2% FeCl 3 contained in both samples, and the solvation of FeCl 3 was thought to increase the surface energy of the droplets, consequently reducing their volume [ 30 ]. Compared to the CMC/TA−PLA/Fe ( Figure 1 D1) film, the pores on the surface of the CMC−PLA/Fe ( Figure 1 C1) film were smaller, with a porosity of only 3.12%, which was attributed to the limited cross−linking rate of CMC with Fe 3+ compared to the rapid cross−linking of tannins with Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…The pyrrole contained in the humid conditions increases the air/polymer solution interfacial force due to the pyrrole being soluble in water in spite of organic material. Similarly, the addition of metal salt in the polymer solution increases the air/polymer solution interfacial force by increasing the hydrophilicity of the polymer solution. Therefore, the pore size of PCL-Cu film is greatly decreased. However, the PPy polymer coating formed by one-step polymerization during the BF process could inhibit the packing of the water droplet by evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments in the BF method have led to the advancement of the technique by self-assembly followed by additional treatment due to the possibility of combining organic and inorganic compounds. Therefore, the creation of new materials with tailored properties has attracted much attention and considerable literature has grown up around the fabrication of such materials via the modified BF method, summarized in Table 1 [ 70 , 97 , 98 ]. This method usually requires two steps for the pore-selective functionalization of the HCP films.…”
Section: Pore-selective Functionalization Of Hcp Filmsmentioning
confidence: 99%
“…This method is generally popular for the synthesis of metal NPs, where a metal precursor is added in the polymer solution followed by its chemical reduction using a reducing agent such as sodium borohydride, sodium citrate, citric acid, ascorbic acid, and hydrazine [ 99 ]. For instance, Li et al reported the addition of metal salts, such as HAuCl 4 , AgNO 3 , and CuCl 2 , in the polymer solution to fabricate metal-salt-filled HCP films [ 97 ]. Later, aqueous NaBH 4 was poured onto the prepared films to reduce the metal salts inside the pores to metal NPs filled pores shown in Figure 8 .…”
Section: Pore-selective Functionalization Of Hcp Filmsmentioning
confidence: 99%